2018
DOI: 10.1016/j.sjbs.2017.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora isolation and molecular characterization of Aspergillus and Fusarium species in Tunisian cereals

Abstract: Wheat, barley and maize are the mainly consumed cereals in Tunisia. This study aimed to determine the mycoflora of these cereals with special focus on the mycotoxigenic and species. Freshly harvested samples and other stored samples of each type of cereal (31 and 34 samples, respectively) were collected in Tunisia and cultured for fungal isolation and identification. Identification of fungal genera was based on morphological and species were identified by species specific PCR assays complemented with DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 44 publications
5
16
0
Order By: Relevance
“…This result similar to the data were recorded by Jedidi et al. (2018) who revealed that discrimination of the two species of the A . niger aggregate ( A .…”
Section: Resultssupporting
confidence: 93%
“…This result similar to the data were recorded by Jedidi et al. (2018) who revealed that discrimination of the two species of the A . niger aggregate ( A .…”
Section: Resultssupporting
confidence: 93%
“…The dominance of A. flavus have been reported in other commodities from Algeria such as wheat and wheat products (Riba et al, ), dried fruits (Ait Mimoune et al, ), peanuts (Guezlane‐Tebibel et al, ), and spices (Azzoune et al, ). Similar results were shown in other African countries like Tunisia for cereals (Jedidi et al, ; Jedidi, Cruz, González‐Jaén, & Said, ), and Tunisian vineyards (Melki Ben Fredj et al, ), Morocco for wheat grains (Hajjaji et al, ) and Nigeria for maize and marketed poultry feed (Atehnkeng et al, ; Ezekiel, Atehnkeng, Odebode, & Bandyopadhyay, ).…”
Section: Discussionsupporting
confidence: 78%
“…This approach has been confirmed by several authors, including Mehta et al [28], which have been reported to be dominated by mesophilic fungi, such as Aspergillus, Fusarium and Mucor during the later stages of composting. For fungal successions, a decay agent can replace other species when changes in the substrate have interacted with changes in saprophytic competitiveness and inoculum potential, giving it a decisive advantage [29,30].…”
Section: Moldsmentioning
confidence: 99%